2020
DOI: 10.9734/jocamr/2020/v12i130199
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Evaluation of Antiviral Activity of some Nigerian Medicinal Plants on SARS-CoV-2Combinatorial Evaluation of Antiviral Activity of some Nigerian Medicinal Plants on SARS-CoV-2

Abstract: The coronavirus disease COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) has presented unprecedented challenges to the healthcare systems in the world. There are no definite effective therapeutic agents or vaccines against the virus currently. However clinical management of the infection includes prevention, control measures, supportive care and repurposed drug therapy based on pathophysiology of the virus and manifestation of the disease condition thereby using antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The cited constituent was present at a highest percentage in the active sage oil (10.2%). Falang carried out an in silico investigation of the plant constituents of some Nigerian medicinal species [48]. The authors showed that the phytochemical constituents of the selected plants had better binding affinity to several Covid-19 viral target proteins, testing the S. officinalis EO compounds borneol, camphor, and pinene.…”
Section: Essential Oil Analysesmentioning
confidence: 99%
“…The cited constituent was present at a highest percentage in the active sage oil (10.2%). Falang carried out an in silico investigation of the plant constituents of some Nigerian medicinal species [48]. The authors showed that the phytochemical constituents of the selected plants had better binding affinity to several Covid-19 viral target proteins, testing the S. officinalis EO compounds borneol, camphor, and pinene.…”
Section: Essential Oil Analysesmentioning
confidence: 99%